An exploratory study of degree course objectivity and graduate performance : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Russell, Sarah (Massey University, 1992)
This study looks at the issue of degree course objectivity from the perspective of Science and non-Science lecturers. It is an exploratory piece of research, and focuses on a sample of degree courses offered in New Zealand universities. Research was conducted in several steps, and involved the completion of two questionnaires. Participants were also asked to supply a written statement outlining the objectivity of assessment in their own teaching domain. The t-test statistic was used to measure the significance of research findings. In New Zealand, university lecturers recognise that a difference exists in the objectivity of degree course content. Further, they are aware that Science oriented courses lend themselves to greater assessment objectivity than the non-Sciences, despite disagreeing over the exact level of objectivity in the latter field of study. The variance in degree course objectivity has a potential impact on the distribution of 'good' degrees awarded across university departments, yet has not evoked the amount of attention amongst academics that it clearly merits. It is concluded, that in New Zealand, research must continue into the issue of subject matter objectivity as a potential impact on students' degree selection and employee recruitment.
Keywords: Evaluation; New Zealand; University and colleges; Degrees, Academic